GGC Repeat Expansion of NOTCH2NLC in Adult Patients with Leukoencephalopathy. Issue 6 (22nd October 2019) - Okubo, Masaki; Doi, Hiroshi; Fukai, Ryoko; Fujita, Atsushi; Mitsuhashi, Satomi; Hashiguchi, Shunta; Kishida, Hitaru; Ueda, Naohisa; Morihara, Keisuke; Ogasawara, Akihiro; Kawamoto, Yuko; Takahashi, Tatsuya; et al.
Abstract : Leukoencephalopathies comprise a broad spectrum of disorders, but the genetic background of adult leukoencephalopathies has rarely been assessed. In this study, we analyzed 101 Japanese patients with genetically unresolved adult leukoencephalopathy using whole‐exome sequencing and repeat‐primed polymerase chain reaction for detecting GGC expansion in NOTCH2NLC . NOTCH2NLC was recently identified as the cause of neuronal intranuclear inclusion disease. We found 12 patients with GGC expansion in NOTCH2NLC as the most frequent cause of adult leukoencephalopathy followed by NOTCH3 variants in our cohort. Furthermore, we found 1 case with de novo GGC expansion, which might explain the underlying pathogenesis of sporadic cases. ANN NEUROL 2019;86:962–968